Longshengzhi Capsules Improve Ischemic Stroke Outcomes and Reperfusion Injury via the Promotion of Anti-Inflammatory and Neuroprotective Effects in MCAO/R Rats. (9th March 2020) - Yang, Weinan; Zhang, Lincheng; Chen, Simiao; Yao, Qigu; Chen, Haihong; Zhou, Jing; Chen, Weiyan; He, Lan; Zhang, Yuyan
Abstract : Stroke is the leading cause of death in the elderly. Traditional Chinese medicine provides an exciting strategy for treating stroke. Previous reports indicated that Longshengzhi capsules (LSZ), a modified Chinese formula, reduced formed thrombi and oxidative stress and were promising in the clinical treatment of ischemic stroke. However, the specific therapeutic effect and mechanism of LSZ are still ambiguous. This study aimed to define the effects of LSZ on proinflammatory mediators and neuroprotective effects on middle cerebral artery occlusion and refusion (MCAO/R) rats. Rats were treated with different doses of LSZ (0.54, 1.62, and 4.32 g/(kg·d)) in a week after model building. LSZ could improve the survival rate, ischemic stroke outcome, and infarct volume. In addition, significant decrease was observed in reactive oxygen species (ROS) levels and inflammatory factor levels in LSZ-treated groups, concomitant with increase in activities of superoxide dismutase (SOD), neurosynaptic remodeling, and decrease in brain edema. It is proposed that LSZ has anti-inflammatory and neuroprotective effects resulting in downregulating matrix metalloproteinase 2/9 (MMP-2/9) and vascular endothelial growth factor (VEGF) and nuclear factor kappa-B (NF- κ B) and upregulating microtubule-associated protein-2 (Map-2) and growth-associated protein-43 (GAP-43) via p38 MAPK and HIF-1 α signaling pathways in MCAO/R rats. This study provides potential evidences that p38 MAPK and HIF-1 α /VEGF signaling pathways play significant roles in the anti-inflammatory and neuroprotective effects of LSZ.